(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background : Medical course and dentistry have always been considered to be stressful to the students because of its depth, diversity and competitiveness. These are very extensive course spread 4 to 5 years in India. Stress sometimes can lead to anger, which cause even more stress. Prolonged stress and anger can take a toll on the students, both physically and emotionally. It is important to eliminate them by attempting control management and implication of positive coping strategies Aim : This study aims to investigate level and source of stress, anger, anxiety, depression and associated coping mechanisms among dental students Material and method : A link to an online questionnaires conducted through Surveymonkey was distributed among all third-year, fourth-year and final-year students. Result : The first major stressor for the dental students was clinical requirements (61.3%) followed by patient’s behavior, peer pressure/competitiveness, education program and language barrier. Taking some time off to rest (20.3%), talking to a friend (%23.9) and listening to music (19%) were the most commonly reported coping mechanisms (Table 3). Conclusion : The primary sources of stress as perceived by the dental students were peer pressure/ competitiveness, patient’s behavior and clinical requirements. In the present study, female dental students reported higher stress levels and a wider range of coping than male students, hence a stress management program should be implemented that focusing towards dental students. The preventive and intervention must be sought and directed as this need early in the student years.